Prognostic factors for return-to-work following surgery for carpal tunnel syndrome: a systematic review. (September 2016) - Peters, Susan; Johnston, Venerina; Hines, Sonia; Ross, Mark; Coppieters, Michel
EXECUTIVE SUMMARY: Background: Carpal tunnel syndrome (CTS) is a common problem, that can be effectively managed by surgery. Screening for prognostic factors is important to identify workers who are at a greater risk of a poor work outcome in order to implement tailored interventions to facilitate their return-to-work. Objective: To synthesize the best available evidence on the association of preoperative prognostic factors with work-related outcomes in people who have undergone carpal tunnel surgery. Inclusion criteria Types of participants : Participants included those who were employed at the time of surgery, underwent carpal tunnel surgery and planned to return-to-work. Outcomes : The primary outcome was return-to-work. Types of studies : Quantitative studies investigating at least one prognostic factor for a work-related outcome in studies of workers who had carpal tunnel surgery were considered. Search strategy: Eleven electronic databases were searched from their respective inception date up to July 2015. A total of 3893 publications were reviewed. Methodological quality: The quality of the included studies was assessed by two reviewers using a modified version of an appraisal tool (Joanna Briggs Institute Meta-analysis of Statistical Assessment and Review Instrument [JBI-MAStARI]). The following criteria were evaluated: study population representativeness, clearly defined prognostic factors and outcomes, potential confounding variables and appropriate statistical analysis. Data extraction: Data extraction was performed using a modified version of the standardized extraction tool from JBI-MAStARI. Data synthesis: Statistical pooling was not possible. Findings are presented in tables and narrative format. Results: Eleven studies (13 publications) investigating 93 prognostic factors for delayed return-to-work or prolonged work disability outcomes and 27 prognostic factors for work role functioning in 4187 participants were identified. Prognostic factors associated with workers' increased likelihood of an earlier return-to-work in a moderate-to-high-quality study included worker expected or desired fewer days off work, occupation, lower pain anxiety and if CTS had not altered their work role. Prognostic factors for a poorer work-related outcome included older age, lower household income, greater upper extremity functional limitation, greater than two musculoskeletal pain sites, lower recovery expectations, worse mental health status, job accommodation availability, high job strain, high job demands with high job control, poor co-worker relationships, poor baseline work role functioning, less-supportive workplace policies, preoperative work absence due to CTS or work disability of any cause, workers' compensation status, attorney involvement, and post-diagnosis surgical wait time. Conclusion: For workers who have had carpal tunnel surgery, there are a number of factors which may be modified in order to improve return-to-work times.